1981
DOI: 10.1055/s-2008-1063280
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Anomalous Pancreaticobiliary Ductal Union in Canine Models

Abstract: For the purpose of resolving the mechanism of the ill-effect of refluxed pancreatic juice, due to the anomalous pancreaticobiliary ductal union, canine models were produced. Mongrel adult dogs and puppies were used. Pancreatico-cholecystostomy was performed on 5 adult dogs and 5 puppies. Pancreatico-choledochostomy was performed on 10 adult dogs and 5 puppies. In both procedures, the cylindrical dilatation of the choledochus resulted. The pathological changes in the choledochus were very similar to the cylindr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…It has been shown that in humans the existence of PBM results in an elevated amylase concentration in bile. Other pancreatic enzymes, such as trypsin and elastase, have also been shown to be in an activated state under such circumstances [23]. There is also evidence that no activation of trypsin ensued in vitro from simply allowing the enzyme to intermingle with bile, which normally contains no enterokinase.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that in humans the existence of PBM results in an elevated amylase concentration in bile. Other pancreatic enzymes, such as trypsin and elastase, have also been shown to be in an activated state under such circumstances [23]. There is also evidence that no activation of trypsin ensued in vitro from simply allowing the enzyme to intermingle with bile, which normally contains no enterokinase.…”
Section: Discussionmentioning
confidence: 99%
“…Various animal models to simulate the disease process in humans have been used to investigate the pathogenesis of cystic and fusiform CCs. However, anastomosis of the pancreatic and biliary ducts, which allow pancreatic juice to enter the bile duct, only resulted in mild dilation of the common bile duct without cystic dilatation[ 4 ]. Moreover, even in large animal models, such as minipigs, no one was observed to have dilatation of the bile ducts[ 5 ].…”
Section: Introductionmentioning
confidence: 99%